2013
DOI: 10.1158/0008-5472.can-12-3516
|View full text |Cite
|
Sign up to set email alerts
|

Radioresistant Cancer Cells Can Be Conditioned to Enter Senescence by mTOR Inhibition

Abstract: Autophagy is frequently activated in radioresistant cancer cells where it provides a cell survival strategy. The mTOR inhibitor rapamycin activates autophagy but paradoxically it also enhances radiosensitivity. In this study, we investigated the mechanisms of these opposing actions in radiation-resistant glioma or parotid carcinoma cells. Radiation treatment transiently enhanced autophagic flux for a period of 72 hours in these cells and treatment with rapamycin or the mTOR inhibitor PP242 potentiated this eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 50 publications
3
28
0
Order By: Relevance
“…During this period, the senescence-associated β-galactosidase activity also showed that premature senescence has been initiated, caused by the inhibition of mechanistic target of rapamycin (mTOR) pathway. Similar results have also been obtained in tumour xenografts [8]. …”
Section: Relation Of Autophagy To Cancersupporting
confidence: 88%
“…During this period, the senescence-associated β-galactosidase activity also showed that premature senescence has been initiated, caused by the inhibition of mechanistic target of rapamycin (mTOR) pathway. Similar results have also been obtained in tumour xenografts [8]. …”
Section: Relation Of Autophagy To Cancersupporting
confidence: 88%
“…Additionally, senescence induced by hyperactivation of Akt was mediated through mTORC1, although details regarding the involvement of autophagy in this mechanism need to be elucidated [23]. Moreover, it was observed that combining autophagy inhibitors with radiation treatment could trigger premature senescence in both cancer cells and xenograft models, which is an approach to restoring radiosensitivity [24].…”
Section: Autophagy and Senescencementioning
confidence: 99%
“…This radiation-enhancing effect seems to result from heterochromatin remodeling, irreversible growth arrest, and premature senescence. At the cellular level, enhanced radiosensitivity is likely due to the restoration in tumor suppressor RB1 activity and its subsequent suppression of E2F transcription factor 1 (E2F1) activity [3,4]. For prostate cancer, which is considered relatively radio-resistant, treatment with the phorbol ester, 12- O -tetradecanoylphorbol 12-acetate (TPA), can also enhance radiation-induced cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%